2015
DOI: 10.4103/0019-509x.178389
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of Breastlight in detection of breast lesions

Abstract: The results of this study showed that the efficacy of Breastlight in detection of breast changes as domestic apparatus was appropriate. However, it is recommended further studies to evaluate the Breastlight efficacy and accuracy in detection of the BLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…[1] In Iran, a study done to compare results using the breast light with those from clinical breast examination (CBE), mammography or ultrasound showed that the breast light missed 40% of the cancers picked up by CBE or mammography. [2] A small study from Iraq showed a false-negative rate of 19.4% and a false-positive rate of 46.3%. The study concluded that these findings preclude the use of the breast light as a screening tool for breast cancer.…”
Section: Breast Lightmentioning
confidence: 97%
See 1 more Smart Citation
“…[1] In Iran, a study done to compare results using the breast light with those from clinical breast examination (CBE), mammography or ultrasound showed that the breast light missed 40% of the cancers picked up by CBE or mammography. [2] A small study from Iraq showed a false-negative rate of 19.4% and a false-positive rate of 46.3%. The study concluded that these findings preclude the use of the breast light as a screening tool for breast cancer.…”
Section: Breast Lightmentioning
confidence: 97%
“…The most recent publication found was in 2015 in the Indian Journal of Cancer, where only 35.8% of lesions that were detected by mammography were detected by the breast light. [2] On its SA website, the breast light is advertised as a self-examination adjunct and comes with a disclaimer that 'Breastlight is not capable of detecting all sizes, positions and types of breast abnormalities. It is not intended for use as a diagnostic device.…”
Section: Breast Lightmentioning
confidence: 99%
“…A tool that is portable and battery operated will facilitate its use in remote locations in the developed world as well as in low and middle-income countries. [28,[32][33][34][35]37] The complete wish-list of the requirements of a practical tool for the rapid diagnosis of breast cancer is shown in Table 1.…”
Section: Portabilitymentioning
confidence: 99%
“…Transillumination imaging has been studied using a commercial tool such as Breastlight [29,30] and has been found to have varying sensitivities between 60% and 93% for breast cancer detection, primarily due to the dependency on the skill of the clinician to visually analyze the transillumination images. [28,[30][31][32][33][34][35][36] Mehnati et al [37] and Edge et al [38] critically review the transillumination imaging for breast screening and recommended performing more clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…A smaller study involving 310 females shows almost equal sensitivity between Breastlight and mammography in detecting breast cancer [ 29 ]. Another report using 500 women from Iran also reported the efficacy of BreastLight in detection of breast changes [ 30 ]. However, BreastLight could not penetrate easily dense breasts of young African women and women who were very dark in complexion.…”
Section: Introductionmentioning
confidence: 99%